United States : Financial Sector Assessment Program-Technical Note-Financial Crisis Preparedness and Deposit Insurance. (IMF Staff Country Reports; Country Report ;, 2020)
The U.S. authorities should preserve the considerable progress in the resiliency, recoverability, and resolvability of financial companies and insured depository institutions (IDIs), and intensify financial crisis preparedness efforts. After a decade of resolution planning, the development of the U.S. resolution regime is more advanced than in other major economies. This regime, together with the strong track record of the deposit insurance system (DIS) for banks and the federal banking agencies' (FBAs) preparation for resolution, provide a strong foundation for crisis preparedness. Bank holding companies (BHCs) have integrated recovery and resolution planning (RRP) into business-as-usual (BAU) activities, increasing their resiliency; this process has deepened the FBAs' understanding of the BHCs' business models and RRP capabilities. The FBAs should continue their own annual resolution planning and mitigate the recent changes that reduced the BHCs' RRP. These efforts should be complemented by further interagency crisis preparedness, including particularly with the U.S. Department of the Treasury (UST), given its essential role in critical aspects of crisis responses. Finally, further refinements relating to cross-border resolution also deserve attention.